Evaluation of Liposome-Encapsulated Vancomycin Against Methicillin-Resistant Staphylococcus aureus - Enkhtaivan Erdene; Odonchimeg Munkhjargal; Galindev Batnasan; Enkhjargal Dorjbal; Baatarkhuu Oidov; Ariunsanaa Byambaa (Biomedicines)
Background/Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) is a global health concern due to its resistance to conventional antibiotics. This study evaluated the efficacy of liposome-encapsulated vancomycin against MRSA using phospholipids extracted from egg yolk. Liposomes were prepared via the freeze–thaw method, yielding vesicles with an average diameter of 157.01 ± 33.04 nm and a polydispersity index (PDI) of 0.0442, indicating uniformity and stability. Antibacterial activity was assessed using the microdilution method. Liposome-encapsulated vancomycin demonstrated complete bacterial growth inhibition (100%) against MRSA ATCC 2758 at dilutions of 101 and 102, compared to only 50% inhibition by free vancomycin at 101. At higher dilutions (103), liposome-encapsulated vancomycin maintained 70% inhibition, whereas free vancomycin was ineffective. In vivo studies using a murine wound infection model revealed that wounds treated with liposome-encapsulated vancomycin achieved superior healing, with complete tissue regeneration observed by day 14. Histological analysis showed reduced inflammation and enhanced tissue recovery in liposome-encapsulated vancomycin-treated groups, compared to fibrosis and persistent necrosis in free vancomycin-treated groups. By enabling sustained drug release and improved bioavailability, liposomal formulations minimized required dosages and systemic toxicity, reducing the risk of resistance development. This study highlights the clinical potential of liposome-encapsulated vancomycin as a scalable, cost-effective treatment for MRSA, particularly in resource-limited settings.